The effects of dental health education intervention of PTA members in improving the dental health of public elementary schoolchildren in West Jakarta. - Chandrasari, Winny (Thesis - (Doctor of Public Health) - University of the Philippines Manila)
Based on the results of an evaluation survey of the School Dental Program in Jakarta done 1988, it was found out that the dental health of elementary school children in Jakarta is still below par in terms of the goals of School Dental Health Program (SDHP).
Identified as the cause of the problem was weak implementation and hence low compliance to the School Dental Program, and there was no active involvement of parents to strengthen the program.
This study was designed to investigate the effects of Parents and Teachers Association (PTA) involvement in the attempt to attain the School Dental Program goals.
The Quasi-experimental design with time-series observations was used with three packages of intervention: 1. Seminar workshop plus Enter-educate; 2. Seminar workshop plus Home-visits; 3. Seminar workshop only.
The respondents were 256 mothers from four randomly selected public elementary schools in West Jakarta, and the intervention was conducted for six months, with pre-test observation and two post-test observation every three months.
Results show that there were statistically significant differences between the experimental schools and the control in the increase of mothers' KAP score, the reduction of their children's oral hygiene score, decrease of children's Decayed-teeth score, increase of children's Filled-teeth score, increase in the attendance of parents in SDHP activities, and increase of visits by schoolchildren to the SDHP dental clinic.
There are difference in the effects of the three packages of intervention, with the Enter-educate package showing better sustainance of KAP score; the Home-visit package with more reduction in the children's oral hygiene score; and the Seminar-workshop with less attendance of respondents in SDHP activities.
Keywords: Dental Health Services -- Jakarta; Children -- Dental care